A Substrate-Activated Efflux Pump, DesABC, Confers Zeamine Resistance to Dickeya zeae - Zhibin Liang (American Society for Microbiology, 2019)
ABSTRACT Zeamines are a family of polyamino phytotoxins produced by Dickeya zeae EC1. These phytotoxins are also potent antibiotics against a range of microorganisms. To understand how D. zeae EC1 can protect itself from the antimicrobial activity of zeamines, we tested whether the ABC transporter genes within the zms (zeamine synthesis) gene cluster were related to zeamine resistance. Our results ruled out the possible involvement of these ABC transporters in zeamine resistance and instead unveiled an RND (resistance-nodulation-cell division) efflux pump, DesABC, which plays an important role in zeamine resistance in D. zeae EC1. The desAB genes are located next to the zms gene cluster, but desC is at a distant location in the bacterial genome. Null mutation of the desABC genes in a zeamine-minus derivative of strain EC1 led to about an 8- to 32-fold decrease in zeamine tolerance level. This efflux pump was zeamine specific and appeared to be conserved only in Dickeya species, which may explain the high potency of zeamines against a wide range of bacterial pathogens. Significantly, expression of the desAB genes was abolished by deletion of zmsA, which encodes zeamine biosynthesis but could be induced by exogenous addition of zeamines. The results suggest that sophisticated and coordinated regulatory mechanisms have evolved to govern zeamine production and tolerance. Taken together, these findings documented a novel signaling role of zeamines and the first resistance mechanism against zeamines, which is a family of potent and promising antibiotics against both Gram-positive and Gram-negative bacterial pathogens. IMPORTANCE Zeamines are a family of newly identified phytotoxins and potent antibiotics produced by D. zeae EC1. Unlike most bacterial organisms, which are highly sensitive, D. zeae EC1 is tolerant to zeamines, but the mechanisms involved are unknown. Our study showed, for the first time, that a new RND efflux pump, DesABC, is indispensable for D. zeae EC1 against zeamines. We found that the DesABC efflux pump was zeamine specific and appeared to be conserved only in the Dickeya species, which may explain the high potency of zeamines against a wide range of bacterial pathogens. We also showed that expression of DesABC efflux system genes was induced by zeamines. These findings not only provide an answer to why D. zeae EC1 is much more tolerant to zeamines than other bacterial pathogens but also document a signaling role of zeamines in modulation of gene expression.